Living with the dead - Harrington, Nicola (Studies in Funerary Archaeology, 2013)
Living with the Dead presents a detailed analysis of ancestor worship in Egypt, using a diverse range of material, both archaeological and anthropological, to examine the relationship between the living and the dead. Iconography and terminology associated with the deceased reveal indistinct differences between the blessedness and malevolence and that the potent spirit of the dead required constant propitiation in the form of worship and offerings. A range of evidence is presented for mortuary cults that were in operation throughout Egyptian history and for the various places, such as the house